Effects of lindane as an endocrine disruptor chemical on human health - Rozita, H.,; Hasni, M.J, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
Over the past decades, a number of substances in the environment have been detected to have detrimental effects on the endocrine system. These substances have been labeled as endocrine disruptor chemicals (EDC) as they mimic or block hormones function and therefore, disrupt the normal body physiological functions. Effects on human beings include decrease in sperm counts and quality, cryptorchidism, hypospadias, testicular and male breast cancer,impairment of ovulatory mechanism and cardiovascular system. One of the examples of these EDC is lindane, a 99% pure gamma isomer of hexachlorocyclo-hexane. Exposures to lindane are either through dermal contact, inhalation or ingestion. Acute toxicity symptoms include headache, gastrointestinal symptoms, convulsion, cyanosis and circulatory collapse. Chronic symptoms include blood disorders, convulsion and disruption of the endocrine system particularly the reproductive system. Lindane has also been anticipated as a carcinogen. The International Agency for Research in Cancer (1991) has classified lindane as Class 2B carcinogen. The United States Environmental Protection Agency (USEPA) has set a maximum contaminant level of 0.2 parts per billion (ppb) in drinking water. Acceptable daily intake (ADI) for lindane by Codex Alimentarius is 0.001 mg / kg body weight per day. Due to its endocrine disruptor characteristic and carcinogen effects, there is a need for a rapid elimination of lindane usage in the pharmaceutical, veterinary and agricultural today. We also need an effective delivery of education programme about the risk of lindane, emphasizing the protection of exposed groups of children, indigenous people and workers.